2019
DOI: 10.1016/j.foodchem.2019.05.178
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of goat milk kefir: Profiling the fermentation-time dependent protein digestion and identification of potential peptides with biological activity

Abstract: Kefir is a fermented dairy product, associated to health benefits because of being a probiotic and due to the presence of molecules with biological activity. In this work, we have profiled the peptide composition of goat milk kefir at three different fermentation times using a peptidomics approach, in order to study changes in peptide concentrations and patterns of protein digestion throughout the fermentation time. We identified 2328 unique peptides corresponding to 22 protein annotations, with a maximum of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 38 publications
3
47
3
1
Order By: Relevance
“…The highest quantitative reduction of indicator microorganisms in the case of fermented whey was found in the fermented whey by Lactobacillus parakefiri. The study conducted by Izquierdo-González et al [14] indicated that 24 h fermentation of goat's milk by kefir microflora maximizes the variety of peptides with potential biological activity. Lactobacillus kefiranofaciens subsp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest quantitative reduction of indicator microorganisms in the case of fermented whey was found in the fermented whey by Lactobacillus parakefiri. The study conducted by Izquierdo-González et al [14] indicated that 24 h fermentation of goat's milk by kefir microflora maximizes the variety of peptides with potential biological activity. Lactobacillus kefiranofaciens subsp.…”
Section: Resultsmentioning
confidence: 99%
“…There are few data describing the functional properties of bioactive compounds released during the fermentation of goat's milk with kefir grain microflora. Kefir grain microflora consisting of bacteria of the genus Lactobacillus, Lactococcus and yeast of the genus Kluvermyces and Saccharomyces connected extruded exopolysaccharide matrix-kefiran produced by Lactobacillus kefiranofaciens [14]. The aim of the study was to evaluate the antibacterial properties of biologically active compounds released during the fermentation of goat's milk by selected bacterial strains that are part of the kefir grain microflora.…”
Section: Introductionmentioning
confidence: 99%
“…Different bioactivities of kefir were reported in literature, however, identification and characterization of such peptides is limited. Izquierdo-González et al (2019) profiled the bioactive peptides in goat milk kefir after 12, 24 and 36 h of fermentation using peptidomics approach. In total, 11 bioactive peptides (Table 4) were identified after different fermentation time; however, maximum concentration was obtained after 24 h which decreased thereafter.…”
Section: Kefir and Koumissmentioning
confidence: 99%
“…Although LAB assimilate the resultant peptides for growth, a large number of peptides are still remained and accumulated during fermentation. By far, the commonest BPs found in the fermented milk are the angiotensin‐converting enzyme inhibitory (ACE‐I) peptides (Chen et al., 2015; Izquierdo‐González et al., 2019; Rai et al., 2017). As shown in Table 1, the main trend reflects a general penchant for using LAB in animal's milk fermentation.…”
Section: Sourcesmentioning
confidence: 99%
“…Recently, Izquierdo‐González et al. (2019) produced kefir by fermenting goat's milk for different period of time (0, 12, 24, and 36 hr) at 25 °C under aerobic condition with 5% (w/v) kefir grains. The LC–MS/MS analysis revealed that 2,004 peptides were discovered, among which 11 peptides were identified with bioactivities (antibacterial, antioxidative, dipeptidyl peptidase IV [DPP‐IV] inhibitor, ACE‐I, and antithrombotic properties) after 24 hr of fermentation.…”
Section: Sourcesmentioning
confidence: 99%